Pemberian Enzim Papain dengan Dosis yang Berbeda pada Pakan Rucah terhadap Pertumbuhan dan Kelangsungan Hidup Benih Ikan Napoleon (Cheilinus undulatus) - Muhammad Agi Saputra Agi; Wiwin Kusuma Atmaja Putra; Tri Yulianto (Intek Akuakultur, 2021)
This study aims to determine the dosage of different papain enzymes in trash feed to increase the survival and seed growth of Napoleon Cheilinus undulates fish. This research was conducted in December 2019 - January 2020 at the Napoleon fish rearing location in Kiabu Village, South Siantan, Anambas Islands Regency. The method used was experimental with a completely randomized design (CRD) with 4 treatments and 3 replications. Where K: without the enzyme, A: 6% the enzyme papain, B 7% the enzyme papain, C: 9% the enzyme papain. Data analysis using One-Way ANOVA and Duncan's Test. Showed the best growth was obtained in treatment C (administration of 9% papain enzyme) with the results of absolute weight growth of ((0.329 Â± 0.020g) and survival (100 Â± 0.00%) The results showed that 9% C treatment was the best treatment for growth.